Field Calibration of Fatigue Models of Cementitiously Stabilized Pavement Materials for Use in the Mechanistic-Empirical Pavement Design Guide. Issue 2 (February 2019) - Li, Xiaojun; Wang, Jingan; Wen, Haifang; Muhunthan, Balasingam
The use of cementitiously stabilized materials (CSM), such as lean concrete, cement-stabilized aggregate, and soil stabilized with cement, lime, fly ash, or combinations thereof in the subgrade, sub-base, and base layers of flexible and rigid pavement structures, is a widely accepted practice by many state highway agencies. However, the bottom-up fatigue cracking models of cementitiously stabilized layers (CSL) described in the AASHTO Interim Mechanistic-Empirical Pavement Design Guide Manual of Practice (referred to as the MEPDG) have not been calibrated for CSM based on their field performance. In addition, top-compression fatigue as well as the effects of increases in the modulus and strength values of CSM over time, erosion, and freeze–thaw and wet–dry cycles on the fatigue properties of CSM are not considered in the MPEDG. To address these deficiencies, this research calibrated the bottom-up fatigue model, and developed and calibrated the top-compression fatigue model, with consideration of modulus and strength growth, erosion, and freeze–thaw and wet–dry cycles. Reasonable correlations between the predicted modulus values and measured modulus values are found for CSL. Further study is needed to refine the calibration and validate the models based on a larger population of field data that covers different material types, climatic zones, and traffic conditions.